TINJAUAN HUKUM BIDANG PEMBINAAN DAN PENGAMANAN TERHADAP ANGGOTA POLRI YANG MELAKUKAN PENYALAHGUNAAN NARKOBA BERDASARKAN PERATURAN PEMERINTAH RI NOMOR 2 TAHUN 2003 TENTANG PERATURAN DISIPLIN ANGGOTA POLRI - Abdul Rokhim, Aulia Tohari dan (Universitas 17 Agustus 1945 Samarinda, 2019)
This study aims to determine criminal liability before entering generalcriminal acts against members of the national police who commit drugabuse and to find out the process of sentencing against members of thenational police who commit drug abuse.The criminal act of narcotics abuse committed by members of theIndonesian National Police is also a violation of disciplinary regulationsand the Polri Professional Code of Ethics, therefore Article 12 paragraph(1) of Government Regulation Number 2 of 2003 concerning DisciplinaryRegulations of Members of the Indonesian National Police confirms that